Pengembangan Buku Saku Geowisata untuk Meningkatkan Keterampilan Pemanduan Pokdarwis Cikahuripan, Lembang - Andari, Rini; Wulung, Shandra Rama Panji; Anggraini, Syifa Putri (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This study aims to develop a geotourism pocketbook as a supporting medium to improve the guiding skills of Pokdarwis (Tourism Awareness Group) members in Cikahuripan , Lembang , West Bandung . The research employed the Research and Development (R&D) method with a Need-Based Development model, involving 10 Pokdarwis members as research subjects using observation, interviews, pretest-posttest , expert validation, and user response questionnaires as instruments. The findings indicate that the developed geotourism pocketbook has a very good level of validity based on evaluations from geotourism experts, village tourism experts, and academic reviewers. The practicality test showed that 100% of respondents considered the content easy to understand and the design attractive, while 90% stated that the book was very helpful in guiding practices. In terms of effectiveness, the pocketbook successfully improved the average pretest score of 56 to 86.5 in the posttest and enhanced the guiding skills of Pokdarwis members in structuring guiding narratives, delivering accurate geotourism information, and building self-confidence. Therefore, the Cikahuripan Geotourism pocketbook is declared valid, practical, and effective as a learning medium to enhance the guiding competence of Pokdarwis members